1987
DOI: 10.1177/00220345870660091801
|View full text |Cite
|
Sign up to set email alerts
|

Recolonization of Human Tooth Surfaces by Streptococcus mutans after Suppression by Chlorhexidine Treatment

Abstract: In eight subjects who were initially highly colonized with Streptococcus mutans and who used a 1% chlorhexidine gel, the numbers of this organism were suppressed in both plaque and saliva. Bacterial plaque samples were obtained from all tooth surfaces, and the recolonization pattern of S. mutans was studied over a 26-week period. At baseline, 83% of all surfaces harbored S. mutans with buccal surfaces colonized in higher frequency than the others. After chlorhexidine treatment, the proportion of tooth surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
2
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 25 publications
6
42
2
2
Order By: Relevance
“…Daily mouthrinses with chlorhexidine alone reduced levels of infection by mutans streptococci immediately after treatment (T 0 ), afterwards they returned to baseline levels. Despite of some other studies had observed that this reduction had been more prolonged (4,5,11), in our study this fact was not observed probably due to low concentration used. Toxic effects of chlorhexidine on mutans streptococci is due to affect the hydrofobicity (13).…”
Section: Oral Streptococcicontrasting
confidence: 90%
“…Daily mouthrinses with chlorhexidine alone reduced levels of infection by mutans streptococci immediately after treatment (T 0 ), afterwards they returned to baseline levels. Despite of some other studies had observed that this reduction had been more prolonged (4,5,11), in our study this fact was not observed probably due to low concentration used. Toxic effects of chlorhexidine on mutans streptococci is due to affect the hydrofobicity (13).…”
Section: Oral Streptococcicontrasting
confidence: 90%
“…However, 120 days after the treatment period, the levels of these microorganisms showed statistically significant differences from the initial levels (baseline). These results are in agreement with previous studies [13,14,21] which showed a gradual reappearance of Although in all collections performed after treatment with CHX gel, the SM levels significantly differed from the initial levels (baseline), and the results of this study suggest that treatment with CHX gel should be repeated every 60 days, taking into account that for most patients in this study, SM levels observed in this period no longer statistically differ from the level of this microorganism considered high risk for dental caries (≥ 10 5 CFU ml -1 saliva) [3,4] Periods of gel reapplication similar to the present study were established by other authors who evaluated the effect of CHX gel in children with no disabilities. For these patients, CHX gel applications must be repeated in a period ranging from 60 to 90 days [12,17].…”
Section: Discussionsupporting
confidence: 94%
“…This step allowed higher CHX concentrations to exert potent bactericidal effects on the S. mutans, which was evident by the decrease in the levels of salivary streptococci observed in the current experiment. Previous research has shown that the re-colonization of microorganisms following antimicrobial agent use was because of the re-growth of existing bacteria, which had not been removed, and not because of the introduction of new bacteria (37). This may explain the sustained decrease in salivary S. mutans observed over the course of the experimental period in the current study.…”
Section: Discussionmentioning
confidence: 49%
“…58, No. 1, [35][36][37][38][39][40][41][42]2016 Original Effects of chlorhexidine (gel) application on bacterial levels and orthodontic brackets during orthodontic treatment treated with fixed orthodontic appliances (9). Different protocols using antimicrobial agents, particularly chlorhexidine (CHX), have been introduced to help control biofilm formation on teeth and brackets in patients treated with fixed orthodontic appliances (4,10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation